How Does the Campus Environment Influence Everyday Physical Activity? A Photovoice Study Among Students of Two German Universities - von Sommoggy, Julia; Rueter, Jana; Curbach, Janina; Helten, Jessica; Tittlbach, Susanne; Loss, Julika (Frontiers in Public Health, 2020)
Background: Sedentary time is high among university students. Prolonged sitting time and reduced physical activity is linked to a number of health risks, therefore interventions to increase options for physical activity on campuses are of high public health relevance. Evidence about the influence of the campus environment on movement and sedentary behavior of students is scarce. This study explores how the structural and social environment of two university campuses are related to students’ everyday physical activity. Methods: We used the photovoice method to get a thorough insight into students’ daily life on campus. We recruited a total of 46 university students in two German cities (university 1: n=22, university 2: n=24). They were asked to take ≥15 photos of places and situations on their respective campus that facilitate or hinder them to be physically active. The pictures were discussed with the participants in 10 focus groups. Focus group discussions were audio-recorded, transcribed and analyzed using content analysis. Results: Both universities do not exploit their potential of fostering daily physical activity on campus, according to the photos and discussions of the participating students. The vast green spaces offer no cues for movement: easily accessible equipment for sports (fixed or mobile) is lacking, walkways are partially hidden, and the facilities discourage from cycling to and on campus. Social norms induce participants to keep sitting during lectures and learning time. It was also pointed out that indoor hallways and foyers could be put to better use with regard to physical activity. The Photovoice project raised the participants’ awareness of how the context influences their movement behavior, and helped them come up with solutions to make physical activity easier for students of their respective universities. Conclusion: The studied campuses discouraged students from being physically active by missing out on opportunities - indoors and outdoors – for fostering movement, such as designating the greens for games or walks, or providing sufficient lockers for biking gear. The results can serve as a basis to plan custom-made public health interventions.